Faktor- Faktor yang Berhubungan dengan Resiko Depresi Postpartum pada Ibu Nifas di Kota Bandung - Astuti Dyah Bestari; Luruh Westriningrum; Didah Didah; Lani Gumilang; Ariyati Mandiri (Universitas Malahayati Lampung, 2025)
ABSTRACT The postpartum period starts after the birth of the placenta until 6 weeks postpartum. Every postpartum mother will experience psychological adaptations starting from the phases of taking in, taking hold to letting go. Postpartum mothers who fail to adapt to physiological and psychological changes tend to experience emotional problems during the postpartum period. Postpartum depression is a mood disorder that affects the mother after childbirth. The incidence of postpartum depression in 2023 will reach 11% -30% in Indonesia. The prevalence of depression in 2023 in West Java will reach 113,568 residents or around 3.3% with ages ≥15 years. Early detection of postpartum depression, especially in postpartum mothers who have risk factors, is one of the best prevention efforts. Screening can be done using the Edinburgh Postnatal Depression Scale (EPDS) which consists of 10 questions. This study aims to determine the factors associated with the risk of postpartum depression in postpartum mothers in Bandung City. The research uses a quantitative analytical approach with a cross sectional design. The respondents in this study were 74 postpartum mothers who gave birth at the UPTD Community Health Center in Bandung City. Bivariate analysis was carried out using the Spearman Rho and Contingency Coefficient tests. The results of the analysis show a relationship between psychological factors (history of depression), obstetric and pediatric factors (type of delivery, pregnancy complications, premature birth), sociodemographic factors (education, economic status) and marital status (domestic violence and unplanned pregnancy) on risk of postpartum depression (p value 0.05). Physical factors (body mass index), obstetric and pediatric factors (parity), sociodemographic factors (age and occupation) and marital status factors (marital status) showed no relationship with the risk of postpartum depression (p value 0.05). Screening using EPDS is one effort that can be done to detect the risk of postpartum depression. Apart from that, it is necessary to pay attention to the risk factors for postpartum depression early so that the incident can be prevented or treated before it becomes serious. Keywords: Depression, Edinburgh Postnatal Depression Scale, Postpartum ABSTRAK Masa nifas dimulai setelah lahirnya plasenta sampai dengan 6 minggu pascasalin. Setiap ibu nifas akan mengalami adaptasi psikologis mulai dari fase taking in, taking hold hingga letting go. Ibu nifas yang tidak berhasil melakukan adaptasi terhadap perubahan fisiologis dan psikologis cenderung akan mengalami masalah emosional selama masa nifas. Depresi postpartum adalah gangguan suasana hati yang memengaruhi ibu sesudah persalinan. Angka kejadian depresi postpartum tahun 2023 mencapai 11%-30% di Indonesia. Prevalensi depresi tahun 2023 di Jawa Barat mencapai 113.568 penduduk atau sekitar 3,3% dengan usia ≥15 tahun. Deteksi dini terjadinya depresi postpartum khususnya pada ibu nifas yang memiliki faktor resiko menjadi salah satu upaya pencegahan terbaik. Skrining dapat dilakukan menggunakan Edinburgh Postnatal Depression Scale (EPDS) yang terdiri dari 10 pertanyaan. Penelitian ini bertujuan untuk mengetahui faktor-faktor yang berhubungan dengan risiko depresi postpartum pada ibu nifas di Kota Bandung. Penelitian menggunakan pendekatan analitik kuantitatif dengan desain cross sectional. Responden dalam penelitian ini adalah ibu nifas yang bersalin di UPTD Puskesmas Kota Bandung sebanyak 74 orang. Analisis bivariat dilakukan menggunakan uji Spearman Rho dan Contingency Coefficient. Hasil analisis menunjukkan adanya hubungan antara faktor psikologis (riwayat depresi), faktor kebidanan dan pediatrik (jenis persalinan, komplikasi kehamilan, kelahiran prematur), faktor sosiodemografi (pendidikan, status ekonomi) dan status pernikahan (kekerasan dalam rumah tangga dan kehamilan tidak direncanakan) terhadap risiko depresi postpartum (p value 0,05). Pada faktor fisik (indeks massa tubuh), faktor kebidanan dan pediatrik (paritas), faktor sosiodemografi (usia dan pekerjaan) dan faktor status pernikahan (status perkawinan) menunjukkan tidak adanya hubungannya dengan risiko depresi postpartum (p value 0,05). Skrining menggunakan EPDS merupakan salah satu upaya yang dapat dilakukan untuk mendeteksi resiko terjadinya depresi postpartum. Selain itu, perlu diperhatikan faktor-faktor resiko terjadinya depresi postpartum sejak dini agar kejadian dapat dicegah atau ditangani sebelum menjadi parah. Kata Kunci: Depresi, Edinburgh Postnatal Depression Scale, Postpartum